Plant–soil interactions in metal contaminated soils. (January 2015) - Krumins, Jennifer Adams; Goodey, Nina M.; Gallagher, Frank
Abstract: The legacy of industrialization has left many soils contaminated. However, soil organisms and plant communities can thrive in spite of metal contamination and, in some cases, metabolize and help in remediation. The responses of plants and soil organisms to contamination are mutually dependent and dynamic. Plant–soil feedbacks are central to the development of any terrestrial community; they are ongoing in both contaminated and healthy soils. However, the theory that governs plant–soil feedbacks in healthy soils needs to be studied in contaminated soils. In healthy soils, negative feedbacks ( i.e. pathogens) play a central role in shaping plant community structure. However to our knowledge, the nature of feedback relationships has never been addressed in contaminated soils. Here we review literature that supports a plant–soil feedback approach to understanding the ecology of metal-contaminated soil. Further, we discuss the idea that within these soils, the role of positive as opposed to negative plant–soil feedbacks may be more important. Testing this idea in a rigorous way in any ecosystem is challenging, and metal contamination imposes an additional abiotic constraint. We discuss research goals and experimental approaches to study plant–soil interactions applicable to metal-contaminated soils; these insights can be extended to other contaminated environments and restoration efforts. Highlights: Plants, soil organisms and metal contamination interact in dynamic ways. Plant–soil feedback theory may be subject to challenge under contamination. Generalized feedback theory in urban soils requires reference sites and meta-analysis. We have technological tools to study feedback interactions in contaminated soils.